ANALISIS PENGARUH CITRA MEREK, PRODUK, HARGA, DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN (Studi pada Konsumen Bandeng Juwana Elrina) - Yuliantiningsih, Arum; Rahardjo, Susilo Toto (Diponegoro Journal of Management, 2016)
This study aimed to analyze the influence of brand image, product, price, and promotion to purchasing decision study case on consumer of Bandeng Juwana Elrina. This study used four independent  variables  are  brand image,  product,  price,  and  promotion.  purchasing  decision variable as a dependent. Simple random sampling method is used for this research. Sample were collected from 100 respondents who ever had experienced to buy in Bandeng Juwana Elrina. Multiple regression analysis is used for this study. The results showed that brand image, product, price, and promotion have positive and significant effect to purchase decision.